Political-economic cycle models of economy of Greece - Tkáčová, Andrea; Gavurová, Beáta; Kováč, Viliam (Journal of Business Economics and Management, 2018)
The political-economic cycle can be caused as the consequence of the wrong political decisions, made with the aim of re-election and maintaining the political power. These decisions influence the macroeconomic indicators of the country and their presence is problematic in the advanced economies. The main objective of this study is to verify the existence of the political-economic cycle model in the case of Greece and to identify the type of this cycle. The basement is given by the approach of Alesina and Roubini (1992), which observes the relationship between the political dummy variables and the selected macroeconomic variables such as gross domestic product, unemployment rate and inflation rate. The eight linear regression models are developed in the R software environment, while the three of them are opportunistic and the five are ideological. These models are identified as statistically significant and according to the methodology, tested for the presence of serial correlation, heteroscedasticity and residual normality. As the models do not confirm the presence of an opportunistic or ideological political-economic cycle, according to the data, the influence of the political parties on changes in the macroeconomic variables before the election is not proved for the case of Greece.